Parasite manipulation of sexual signalling. - Lau, Angel On Yee. (2011)
Organisms express sexual signals to indicate to potential mates of their intention, health condition and capability in ensuring the subsequent survival and reproduction of its young. Such signals are expressed by traits that organisms possess, such as horns and colourful outer coverings (e.g. birds’ feathers and fishes’ scales). Parasite manipulation is a form of host-parasite relationship in which the parasite specifically alters its host’s appearance and behaviour so as to ensure its own survival, transmission and reproduction. This paper is of significance because three seemingly separate ideas – natural and sexual selection, co-evolution and parasite manipulation, are being associated to describe and explain how parasite manipulation can influence sexual signalling in organisms. In this paper, I gave evidence to illustrate that in host-parasite relationships, the parasite is able to manipulate its host to influence the development of sexual signals, thereby conferring increased survival and reproduction to the host and also the parasite. However, if the parasite manipulation was directed at its non-intended recipient instead, parasite manipulation may result in decreased survival and reproductive success in the parasites.